Kegiatan Keagamaan Sebagai Media Penguatan Kecakapan Sosial: Studi Empiris Pada SMKN 3 Bengkulu - Aisa, Nur; Maryam, Maryam; Giyarsi, Giyarsi (Journal of Innovation in Teaching and Instructional Media, 2025)
Extracurricular activities are activities carried out by students outside of school hours, either after school or at certain times, depending on school policy. The main purpose of this activity is to deepen students’ interests in academic and non-academic fields. This study aims to determine the implementation and implementation of Rohis (Islamic Spirituality) extracurricular activities and their influence on the development of social skills of students at SMKN 3 Kota Bengkulu. The hypothesis of this study is that there is a significant influence between Rohis extracurricular activities and the development of students’ social skills. The data collection method used was a questionnaire to obtain data on Rohis extracurricular activities and social skills. Data analysis was carried out using the Pearson Product Moment formula for instrument reliability and Cronbach’s Alpha for instrument validity. In addition, normality and linearity tests were also used before conducting correlation analysis. The results of the study showed that there was a positive relationship between Rohis extracurricular activities and the development of students’ social skills, with a moderate level of relationship (0.578). Based on the performance of the determination coefficient, Rohis extracurricular activities have a contribution of 33% in influencing the development of students’ social skills, while the other 67% is influenced by other factors such as family, school, and community.